Russia's Chechen war - German, Tracey C., 1971- (RoutledgeCurzon, 2003)
This study looks closely at the Russian Federation in transition, following the collapse of the communist Soviet Union, and the implications of the 1991 Chechen Declaration of Independence in the context of Russia's democratisation project.